Use of NovoSorb Biodegradable Temporizing Matrix in the Management of Complex Scalp Defects - Isla Shariatmadari, MBBS, MSc; John Kiely, BM, BCh; Noemi Kelemen, FRCS (Plast) (Plastic and Reconstructive Surgery, Global Open, 2023)
Summary:. Dermal substitutes have emerged as a potential option in complex wound management. PolyNovo NovoSorb Biodegradable Temporizing Matrix has shown promise in managing partial and full-thickness wounds. We discuss here the successful use of this product in the management of a scalp defect complicated by exposed bone, following wide local excision of a desmoplastic melanoma of the scalp.